Perceived cognitive impairments after critical illness: a longitudinal study in survivors and family member controls. Issue 8 (20th June 2016) - Baumbach, P.; Meissner, W.; Guenther, A.; Witte, O. W.; Götz, T.
Abstract : Background: Many former intensive care unit (ICU) patients report difficulties in cognitive functions especially in their daily life. We aimed to measure perceived cognitive impairments in daily life in survivors of critical illness and their family member controls (FMC). Methods: Perceived cognitive impairments were assessed two times after ICU discharge using an adapted German version of the "Functional Assessment of Cancer Therapy – Cognitive Function" questionnaire. After 3 months, 127 former patients and 52 FMC participated and 103/127 patients and 36/52 FMC were followed up after 6 months. Baseline information was obtained retrospectively. Results: We found no significant differences between the patient sample and FMC, 3 and 6 months after ICU discharge. Based on questionnaire ratings, cluster analysis divided patients and FMC into a cognitively 'impaired' and a 'non‐impaired' cluster. Questionnaire scales differed significantly prior to ICU admission as well as 3 and 6 months after ICU discharge between both clusters. While differences between patients and FMC were less pronounced in the 'non‐impaired' cluster, patients were significantly more impaired than FMC at 3 and 6 months after ICU discharge in the 'impaired' cluster. Discussion: A substantial part of former patients were affected by post‐ICU cognitive impairment in daily life. Pre‐existing cognitive impairments were a risk factor. These patients would probably profit from tailored neurorehabilitative therapy. Therefore, an efficient tool to identify potential patients for neurorehabilitation is needed. The questionnaire revealed good psychometric properties. We recommend a comprehensive validation of the questionnaire in this patient population.